The Beixin Culture: archaeobotanical evidence for a population dispersal of Neolithic hunter-gatherer-cultivators in northern China. (December 2020) - Jin, Guiyun; Chen, Songtao; Li, Hui; Fan, Xianjun; Yang, Aiguo; Mithen, Steven
Abstract: Abstract : According to the 'farming/dispersal' hypothesis, the Early and Mid-Holocene spread of Neolithic material culture in East Asia would have arisen from dispersals of established farming populations. The authors test this hypothesis by considering the Beixin Culture that appeared in the south-west Haidai region of northern China c . 5000 BC, before spreading north and east to the coast over the subsequent millennium. While this culture had architecture, elaborate pottery and other forms of Neolithic material culture, analysis of archaeobotanical evidence from Guanqiaocunnan (4340–3970 BC) suggests an economic base of hunting, gathering and cultivating, rather than a reliance on farming.